HOW TO IMPROVE ENGLISH SPEAKING SKILLS - Kurbanbayev DJ.A; Allanova M. M. qizi (Western European Studies, 2024)
This article delves into effective strategies for enhancing English speaking skills. It explores practical methods to boost fluency, confidence, and overall proficiency in spoken English. By addressing common challenges and providing actionable tips, this article aims to empower language learners in their journey toward mastering spoken English.
Keywords: English; Speaking Skills; Fluency; Confidence